On the Structures and Definitions of Collocations Simultaneously Formed by göz / nazar and deg-, degür-, degnele-, and degnel - Bekir Sarıkaya (Türkiyat Mecmuası)
In the Old Turkish period, the words göz [eye] and tegil- [to be blinded] (with the suffix -Il- passive) form the collocations of gözi tegilmek [to be blinded]. Simultaneously, the phrase isâbetü’l-ʻayn [casting the evil eye] is seen in the Arabic language. In the Middle Turkish period, the Arabic words isabet [hit] and musibet [calamity] and Turkish teg- [reach] and teggüçi [harmful] were used with the same meanings. In the context of nazar degme [be attacked by evil eye], which entered the literature in the Old Anatolian Turkish period, göz began to form collocations using the reflexive suffix -In, such as göz deg- [be affected by the evil eye], gözi degnel [bad eye], gözi degnel olmak [to be envious-eyed], and gözi degnele- [to cast the evil eye]. This study uses the analogy method to analyze the structures and definitions of the terms teglüg/k [blind], teggüçi [trouble], tegür-[touch], tegil-, degne- [to be blinded], degnele- [look with an evil eye], değnek [evil eye], değik [evil eye], and degnel [evil eye] as derived from the verbs göz and teg-. In this context, the study discusses the collocations and their definitions diachronically and simultaneously with the help of the Güncel Türkçe Sözlük [Daily Turkish Dictionary], Misalli Büyük Türkçe Sözlük [Big Turkish Dictionary], Tarama Sözlüğü [Tarama Dictionary], and Derleme Sözlüğü [Compilation Dictionary]. The study then discusses the different analyses of the structures of the words degnel and degnele-. The term göz formed collocations such as a compound verb group, a possessive group, and an adjective phrase with the terms yavuz [ferocious], kem [bad], degnel, isabet, deg-, degür- [touch], degnele-. As a result of the diachronic analysis of these collocations, some have been determined to no longer be used and to have been replaced by other collocations.